Modulation of Hippocampal Gamma Oscillations by Dopamine in Heterozygous Reeler Mice in vitro - Wang, Lu; Zhao, Dandan; Wang, Mengmeng; Wang, Yuan; Vreugdenhil, Martin; Lin, Juntang; Lu, Chengbiao (Frontiers in Cellular Neuroscience, 2020)
The reelin haploinsufficient heterozygous reeler mouse (HRM), an animal model of schizophrenia, has altered mesolimbic dopaminergic pathways, and shares similar neurochemical and behavioral properties with the patients with schizophrenia. Dysfunctional neural circuitry with impaired gamma (γ) oscillation (30–80 Hz) has been implicated in abnormal cognition in patients with schizophrenia. However, the function of neural circuitry in terms of γ oscillation and its modulation by dopamine (DA) has not been reported in HRM. In this study, first, we recorded γ oscillations in CA3 from wild-type mice (WTM) and HRM hippocampal slices, and studied the effects of DA on γ oscillations. We found that there was no difference in γ power between WTM and HRM and that DA increased γ power of WTM but not HRM, suggesting that dopamine modulations of network oscillations in HRM are impaired. Second, we found that N-methyl-D-aspartate receptor (NMDAR) antagonist MK801 itself increased γ power and occluded DA-mediated enhancement of γ power in WTM but partially restored DA modulation of γ oscillations in HRM. Third, inhibition of phosphoinositide 3-kinase (PI3K), a downstream molecule of NMDAR, increased γ power and blocked the effects of DA on γ oscillation in WTM and had no significant effect on γ power but largely restored DA modulation of γ oscillations in HRM. Our results reveal that impaired DA function in HRM is associated with dysregulated NMDAR-PI3K signaling, a mechanism that may be relevant in the pathology of schizophrenia.